All‐Dielectric Silicon Metasurface with Strong Subterahertz Toroidal Dipole Resonance. Issue 19 (11th July 2019) - Zografopoulos, Dimitrios C.; Ferraro, Antonio; Algorri, José Francisco; Martín‐Mateos, Pedro; García‐Cámara, Braulio; Moreno‐Oyervides, Aldo; Krozer, Viktor; Acedo, Pablo; Vergaz, Ricardo; Sánchez‐Pena, José Manuel; Beccherelli, Romeo
Abstract: A single‐layer, all‐dielectric metasurface exhibiting a strong toroidal resonance in the low‐atmospheric loss radio window of the subterahertz W‐band is theoretically proposed and experimentally demonstrated. The metasurface is fabricated on a high‐resistivity floating‐zone silicon wafer by means of a single‐process, wet anisotropic etching technique. The properties of the toroidal mode of both the constituent dielectric elements and the metasurface are rigorously investigated by means of the multipole decomposition technique and full‐wave simulations. The experimental demonstration of such a compact, all‐silicon metasurface opens new venues of research in the investigation of toroidal modes and the engineering of functional millimeter‐wave components, which can be scaled to terahertz and higher frequencies of the electromagnetic spectrum. Abstract : Toroidal resonances are hard to observe in natural materials . Here, an all‐silicon metasurface that exhibits a strong toroidal dipole resonance in the subterahertz W‐band is designed and experimentally demonstrated. Such compact, all‐silicon metasurfaces provide new possibilities for the engineering of functional millimeter‐wave components.